Using health information technology to support the needs of Children with Medical Complexity: Mapping review of consumer informatics applications - Asan, Onur; Elkefi, Safa; Clouser, Katharine N.; Percy, Stephen (Frontiers in Digital Health, 2022)
Background Children with medical complexity (CMC) are fragile populations that require continuous care and supervision. CMC family caregivers experience many challenges trying to address CMC patients' needs which puts these caregivers in a stressful situation that may negatively impact the care of CMC patients. Consumer informatics might help these caregivers in coordinating care. However, few consumer informatics applications explicitly focus on supporting CMC caregivers' needs. Objective This systematic mapping literature review aims to provide an overview and a structured understanding of the consumer informatics designed for CMC and their caregivers. Methods We followed a systematic mapping literature review process to provide an overview of the existing Consumer Informatics literature for CMC, which is the scope of our study. We screened IEEE Xplore, Web of Science, and PubMed databases using a preset list of mesh terms that cover the use of medical informatics by children with medical complexities and their caregivers. The selected articles are peer-reviewed English publications that were empirically validated from January 2002 to January 2022. After selecting and filtering the articles, we analyzed them based on the preset mapping questions using the following criteria: publication year, publication source, research type, contribution type, empirical type, the need addressed, target audience, technology users, and consumer informatics' type. Results The initial search resulted in a number of (N = 2,275) articles, and 17 selected publications were included. The results showed an increasing interest in CMC consumer informatics publications over time. Most of the studies were published in 2021, and feasibility research is the dominant research type. The most used technology was telehealth and telemedicine, followed by mobile health. The technologies addressed various needs, including; coordination & follow-up, medical safety, education & social support, daily living activities, shared decision making, information seeking, and emotional support. Most of the efforts were focused on ensuring good coordination and follow-up. Conclusions CMC consumer informatics is a promising research field to present novel initiatives and approaches to manage the caregivers' workload. Future research should be shifted toward providing more evidence-based studies to examine the effectiveness of CMC consumer informatics solutions and identify the related challenges and limitations.